In and beyond local government: making up new spaces of governance. Issue 4 (3rd July 2020) - Cochrane, Allan
ABSTRACT: In the context of austerity, some of the taken for granted territorial boundaries of local government are being stretched and questioned. Here, these issues are explored with the help of two bodies of evidence: the creation of sets of interlocking arrangements on the edge of the London City region (most recently expressed in proposals for development along what has been identified as the Oxford-Milton Keynes-Cambridge Arc); and the experience of a Mayoral development corporation in the West of London, seeking to take advantage of the possibilities arising from major national and metropolitan investments in transport infrastructure. In both cases, project-based governance coupled with the promise of infrastructural investment, sub-regional visions and plans offer the basis on which new spaces of governance are being put together to fit with shifting economic geographies and changing political priorities. Instead of being institutionally fixed, the spaces of government themselves turn out to be malleable and contested.